Association between body roundness index and myopia among US adolescents: a cross-sectional study of NHANES 2001–2006 - Dongfang Wang; Fang Sha; JiaoJiao Feng; Weihua Su; Guodong Tang; Jike Song; Hongsheng Bi (Scientific Reports)
Abstract Myopia has become a major public health problem affecting the eye health of children and adolescents. Previous studies have already indicated the relationship between obesity and myopia. The aim of this study was to explore the association between Body Roundness Index (BRI), an innovative obesity-related indicator, and myopia. In this study, 3915 participants aged 12–19 years from the 2001–2006 National Health and Nutrition Examination Survey (NHANES) database were selected. Weighted multivariate logistic regression analysis and subgroup analysis were performed to evaluate the association between BRI and myopia. We found a positive correlation between BRI and myopia (odds ratio [OR] = 1.049, 95% confidence interval [CI]: 1.009–1.090, P = 0.022). Specifically, after full adjustment, adolescents in Q4 were 26.1% more likely to develop myopia compared to adolescents in Q1 (OR = 1.261, 95% CI 1.046–1.521, P = 0.022). Subgroup analysis demonstrated positive associations between BRI and myopia in Mexican American adolescents, women, those guardians with educational levels lower than high school, those with poverty income ratio (PIR) < 1.30 and those with high physical activity. Subsequently, smoothed curve analyses were conducted to investigate the trend of correlation between BRI and myopia. There was a general linear trend between BRI and myopia (all P values for trend < 0.001) and nonlinear association (all P for nonlinear < 0.05).